Schiff base metal nanocomplex modified solid electrolyte and preparation method thereof
By using Schiff alkali metal nanocomplex modified solid electrolyte in the negative electrode material of all-solid state batteries, the problems of lithium dendrites are solved and the conductivity is insufficient, achieving higher energy density and cycling stability.
Patent Information
- Application Number
- CN202311479656.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-11-07
AI Technical Summary
During the charging and discharging process of all-solid-state batteries, there are problems such as instability of the negative electrode lithium dendrites, poor compatibility with the oxide positive electrode material and insufficient conductivity, which limits its application.
By ball milling and calcining the Schiff alkali metal nanocomplex with the sulfide solid electrolyte, a solid electrolyte modified from the Schiff alkali metal nanocomplex was prepared and used in the negative electrode material for all-solid state batteries.
This method improves the active site of the electrode, promotes the intercalation and deintercalation of lithium ions, reduces the electrolyte resistance, improves the ion transfer rate, enhances the energy density and cycle life of the battery, improves the interface contact between the electrodes, and improves the electrochemical performance.
Smart Images

Figure CN117438676B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid electrolytes, and in particular to a solid electrolyte modified by a Schiff base metal nanocomplex and a preparation method thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in consumer electronics and electric (automobile) vehicles due to their high energy density. However, their liquid electrolytes are flammable and have caused many safety accidents. Therefore, it is imperative to develop all-solid-state lithium batteries with better safety. As the core of solid-state batteries, electrolytes have developed rapidly. Among all solid electrolytes, sulfide solid electrolytes have better mechanical properties, electrode interface compatibility and the highest room temperature lithium ion conductivity, and have received widespread attention. However, sulfide electrolytes still have problems such as instability with lithium metal negative electrodes, poor compatibility with oxide positive electrode materials and insufficient conductivity, which limit their further application.
[0003] Schiff base, as an organic compound containing electrophilic nitrogen atoms, can form stable complexes with metal ions. Because Schiff base nanometal complexes have the following properties at the nanoscale, 1) Size effect: Nanometal complexes exhibit different properties from other scales due to their nanoscale. For example, nanoparticles have a larger specific surface area, which enhances surface reactions and therefore has higher activity at the electrochemical interface, which helps to improve the charge transfer rate and energy storage density of the material. 2) Electron transport: The electron transport path in nanometal complexes is shorter, which helps to increase the electron conduction rate, thereby enhancing the efficiency of electrochemical reactions. Therefore, the above characteristics provide a theoretical basis for the application of Schiff base nanometal complexes as additives in the battery field. However, the application of Schiff base metal nanocomplexes in the battery field is still in its early stages, and there are few reports on the effects of Schiff base metal nanocomplexes as an additive on the electrochemical performance of the entire battery. Summary of the invention
[0004] In view of this, the purpose of the present invention is to solve the problem of negative electrode lithium dendrites during the charging and discharging process of all-solid-state batteries, and to provide a solid electrolyte material modified by a Schiff alkali metal nanocomplex as an additive and a preparation method thereof.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a solid electrolyte modified by a Schiff alkali metal nanocomplex comprises the following steps: ball-milling a Schiff alkali metal nanocomplex and a solid electrolyte to obtain a mixed powder, and calcining the mixed powder to obtain a solid electrolyte modified by the Schiff alkali metal nanocomplex.
[0007] The metals in the Schiff base nanometal complex include La, Ce, Gd, Ni, Cu, Mn 2 , Co.
[0008] The solid electrolyte is a sulfide solid electrolyte.
[0009] The sulfide solid electrolyte includes Li 3 PS 4 , Li 6 PS 5 Cl, or Li 6 PS 5 At least one of the Cl-doped modified solid electrolytes.
[0010] The mass ratio of the Schiff base nano-metal complex to the sulfide solid electrolyte is (1-7): (60-100).
[0011] Ball to material ratio (10-50): 1. The preferred material weight is 1g-20g.
[0012] The calcination is carried out in a muffle furnace, the calcination temperature is 100°C-800°C, and the calcination time is 2h-15h.
[0013] The preparation method of the Schiff base nano-metal complex comprises the following steps:
[0014] 1) Stir and dissolve the solvent (methanol) and o-vanillin, drop 1,3-phenylenediamine into the mixture, and stir thoroughly to form a Schiff base solution;
[0015] 2) adding a metal salt to a Schiff base solution, stirring and heating, to obtain a metal complex precipitate;
[0016] 3) filtering the metal complex precipitate, washing and drying to obtain a powdery Schiff base nano-metal complex.
[0017] In step 2), the metal salt includes La(NO 3 ) 3 、Ce(NO 3 ), Gd(NO 3 ) 3 ,Ni(NO 3 ) 2 、Cu(NO 3 ) 2 、Mn(NO 3 ) 2 、Co(NO 3 ) 2 At least one of .
[0018] In step 2), the molar ratio of the metal salt to the Schiff base is 1:1-1:2.
[0019] The amount of methanol is 50mL-500mL; the corresponding amount of o-vanillin is 1-5g.
[0020] In step 2) of the present invention, the heating temperature is preferably 50°C-150°C.
[0021] In step 2) of the present invention, the preferred heating time is 30 min-240 min.
[0022] The crystal size of the obtained Schiff base nano-metal complex is about 2nm-20nm.
[0023] As an implementation method of the present invention, the preparation method of the Schiff base metal nanocomplex modified solid electrolyte comprises the following steps:
[0024] The powdered Schiff base nanometal complex is mixed with a sulfide solid electrolyte (such as Li 6 PS 5 Cl) adding the mixture into a zirconia ball mill according to a certain ball-to-material ratio and mixing evenly; then fixing the sealed ball mill on a high-energy planetary ball mill and ball milling at a certain speed for a period of time; scraping the material from the wall of the ball mill, pressing the obtained powder into tablets, vacuum sealing it into a quartz tube, and then placing it in a muffle furnace, heating it to a certain temperature at a certain rate, and then calcining it for a period of time; after cooling to room temperature, grinding the obtained material to obtain a solid electrolyte modified by a Schiff base metal nanocomplex.
[0025] The diameter of zirconia ball milling beads is 1mm-7mm.
[0026] The speed of high energy planetary ball mill is 50r / min-700r / min.
[0027] Ball milling time is 0.5h-10h.
[0028] Heating rate: 0.1℃ / min-2℃ / min.
[0029] The present invention also provides a solid electrolyte with a Schiff base nano-metal complex as an additive for use in an all-solid-state battery.
[0030] The positive electrode material of the all-solid-state battery is NCM811 composite positive electrode material.
[0031] The preparation method of the NCM811 composite positive electrode material comprises the following steps:
[0032] NCM811, the above-mentioned Schiff base metal nanocomplex modified solid electrolyte, and single-walled carbon nanotubes are ball-milled in a mass ratio of (5-7): (4-2): (3-1) to obtain NCM811 composite positive electrode material.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. Schiff base nanometal complexes can provide additional active sites in electrode materials to promote the insertion and extraction of lithium ions. This helps reduce electrolyte resistance and increase ion transfer rate, thereby reducing energy loss and heat generation during charging and discharging. It can also increase the reversible capacity of the electrode and improve the energy density and cycle life of the battery. After multiple cycles, the discharge specific capacity value remains basically unchanged, proving its excellent cycle stability.
[0035] 2. Schiff base nanometal complexes can fill the pores of solid electrolytes, and anion cluster complexes can act as "ion sponges" to absorb a large amount of Li during charging and discharging. + In addition, during the charge and discharge process, a uniform and dense composite conductive layer is formed at the interface between the electrolyte and the negative electrode, which exhibits excellent mechanical stability and avoids the destruction of the SEI film due to the growth of lithium dendrites.
[0036] 3. Sulfide solid electrolytes are very sensitive to air and water. In air and humid conditions, they are very easy to hydrolyze with water in the environment, releasing toxic H 2 S gas and destroy the electrolyte structure, resulting in a decrease in electrolyte ion conductivity; the metal MS bond formed by the introduction of soft acid (Ce, Co, Cu, etc.) in the present invention has good stability to air, H 2 The amount of S gas produced is significantly reduced. However, the PS bond corresponding to P (strong acid) will produce a large amount of H 2 S gas causes electrochemical performance failure.
[0037] 4. The present invention introduces Schiff base nano-metal complexes into the solid electrolyte to fill the pores of the solid electrolyte, while improving the interface contact between electrodes and providing a continuous channel for lithium ion transmission, thereby improving the electrochemical performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0039] Figure 1 is the XRD spectrum of Ce-based Schiff base nanometal complex;
[0040] Figure 2 is the XRD spectrum of Ni-based Schiff base nanometal complex;
[0041] Figure 3 is the XRD spectrum of Co-based Schiff base nanometal complex;
[0042] Figure 4 This is a charge and discharge cycle diagram of a full battery prepared with the material obtained in Example 1 at 0.1C;
[0043] Figure 5 This is a stability test chart of a full battery made from the material prepared in Example 1 after 300 cycles. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0045] Example 1
[0046] 1. Preparation of Ce-based Schiff base nanometal complexes
[0047] 1.1. Take 200 mL of methanol solvent, weigh 3 g of o-vanillin and stir to dissolve, add 0.79 mL of 1,3-phenylenediamine dropwise, and stir thoroughly to form a Schiff base solution.
[0048] 1.2. Weigh 4.06g of cerium nitrate hexahydrate and add it to the Schiff base solution. Stir and heat to 80 degrees Celsius for 2 hours to obtain the corresponding Ce complex precipitate. The whole process requires reflux condensation. Use vacuum filtration to retain the precipitate, use 5°C ethanol to thoroughly wash the precipitate, and then rotary evaporate the precipitate for 20 minutes. After drying, pick out the undissolved orange translucent crystalline impurities and retain only the bright yellow dry powder Ce-based Schiff base nanometal complex (4g). Figure 1 This is the XRD spectrum of Ce-based Schiff base nanometal complex.
[0049] 2. Modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS 5 Preparation of Cl-Ce-L
[0050] The sample of the Schiff base nano Ce complex prepared in step 1 and the Li 6 PS 5Cl, mix evenly in a zirconia ball mill, the total mass of the material is 1g, the ball-to-material ratio is controlled at 30:1, and the diameter of the zirconia ball mill used is 5mm. Then fix the sealed ball mill on a high-energy planetary ball mill and mill it at 550r / min for 7h. Then scrape the material from the wall of the ball mill, press the obtained powder into a tablet, vacuum seal it in a quartz tube, and place it in a muffle furnace for calcination at 550℃ for 7h, with a heating rate of 0.5℃ / min. After cooling to room temperature, take out the modified flaky sulfide solid electrolyte material (Li 6 PS 5 Cl-Ce-L), grind and bottle for later use.
[0051] 3. Preparation of NCM811 composite cathode material
[0052] NCM811, Li prepared in step 2 6 PS 5 Cl-Ce-L, and single-walled carbon nanotubes were weighed into a 25mL zirconia ball mill at a mass ratio of 16:3:1. The total mass of the materials was 1g, the ball-to-material ratio was controlled to 20:1, and the diameter of the zirconia ball milling beads used was 3mm. The sealed ball milling jar was then fixed on a high-energy planetary ball mill at 400r / min for 4h to finally obtain the NCM811 composite cathode material.
[0053] 4. Assembly of all-solid-state batteries
[0054] Weigh 100 mg of modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS 5 Cl-Ce-L) in a 10mm stainless steel tableting mold, press the electrolyte sheet at a pressure of 360MPa, then add 10mg of the composite positive electrode material prepared in step 3 on one side of the electrolyte sheet, press it again at a pressure of 150MPa, then demould it, load it into the solid-state battery test mold, then add a 10mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally load the Al sheet current collector on the positive side and the Cu current collector on the negative side to complete the packaging. Take out the battery mold, put it in the battery fixture, and apply a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature, at a rate of 0.1C, the first cycle charging capacity can reach 209mAh / g.
[0055] Figure 4 and Figure 5 The first charge and discharge cycle diagram of the full battery prepared with the material obtained in this embodiment at 0.1C and the stability test diagram after 300 cycles.
[0056] Example 2
[0057] 1. Preparation of Ni-based Schiff base nanometal complexes
[0058] 1.1. Take 200 mL of methanol solvent, weigh 3 g of o-vanillin and stir to dissolve, add 0.79 mL of 1,3-phenylenediamine and stir well to form a Schiff base.
[0059] 1.2. Weigh 2.71 g of nickel nitrate hexahydrate and add it to the solution. Stir and heat to 80 degrees Celsius for 2 hours to obtain the corresponding Ni complex precipitate. The whole process requires reflux condensation. Use vacuum filtration to retain the precipitate, use 5°C ethanol to fully wash the precipitate, and then rotary evaporate the precipitate for 20 minutes. After drying, pick out the undissolved dark translucent crystalline impurities and retain only the gray-green dry powder Ni-based Schiff base nanometal complex (3g). Figure 2 This is the XRD spectrum of Ni-based Schiff base nanometal complex.
[0060] 2. Modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS 5 Cl-Ni-L)
[0061] Weigh the Ni-based Schiff base nanometal complex prepared in step 2 and the Li 6 PS 5 Cl, mix evenly in a zirconia ball mill, the total mass of the material is 1g, the ball-to-material ratio is controlled at 30:1, and the diameter of the zirconia ball mill used is 5mm. Then fix the sealed ball mill on a high-energy planetary ball mill and mill it at 550r / min for 7h. Then scrape the material from the wall of the ball mill, press the obtained powder into a tablet, vacuum seal it in a quartz tube, and place it in a muffle furnace for calcination at 550℃ for 7h, with a heating rate of 0.5℃ / min. After cooling to room temperature, take out the modified flaky sulfide solid electrolyte material (Li 6 PS 5 Cl-Ni-L), grind and bottle for later use.
[0062] 3. Preparation of NCM811 composite cathode material
[0063] NCM811 and Li prepared in step 2 6 PS 5Cl-Ni-L and single-walled carbon nanotubes were weighed into a 25mL zirconia ball mill according to a mass ratio of 16:3:1. The total mass of the materials was 1g, the ball-to-material ratio was controlled to 20:1, and the diameter of the zirconia ball milling beads used was 3mm. The sealed ball milling jar was then fixed on a high-energy planetary ball mill at 400r / min for 4h. Finally, the NCM811 composite cathode material was obtained.
[0064] 4. Assembly of all-solid-state batteries
[0065] Weigh 100 mg of modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS 5 Cl-Ni-L) is placed in a 10mm stainless steel tableting mold, and the electrolyte sheet is pressed at a pressure of 360MPa. Then 10mg of the composite positive electrode material prepared by the above method is added to one side of the electrolyte sheet, and it is pressed again at a pressure of 150MPa, then demolded and loaded into a solid-state battery test mold, and then a 10mm lithium indium sheet is added to the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally the Al sheet current collector is loaded on the positive electrode side, and the Cu current collector is loaded on the negative electrode side to complete the packaging. Take out the battery mold, put it into the battery fixture, and apply a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature, at a rate of 0.1C, the first cycle charging capacity can reach 180mAh / g.
[0066] Example 3
[0067] 1. Preparation of Co-based Schiff base nanometal complexes
[0068] 1.1. Take 200 mL of methanol solvent, weigh 3 g of o-vanillin and stir to dissolve, add 0.79 mL of 1,3-phenylenediamine and stir well to form a Schiff base.
[0069] 1.2. Weigh 2.71g of cobalt nitrate and add it to the solution. Stir and heat to 80 degrees Celsius for 2 hours to obtain the corresponding Co complex precipitate. The whole process requires reflux condensation. Use vacuum filtration to retain the precipitate, use 5°C ethanol to fully wash the precipitate, and then rotary evaporate the precipitate for 20 minutes. After drying, pick out the undissolved dark translucent crystalline impurities and retain only the red dry powder Co-based Schiff base nanometal complex (3g). Figure 3 This is the XRD spectrum of the Co-based Schiff base nanometal complex.
[0070] 2. Modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS5 Cl-Co-L)
[0071] Weigh the Co-based Schiff base nanometal complex and Li-based nanometal complex prepared in step 1 at a mass ratio of 5:95. 6 PS 5 Cl, mix evenly in a zirconia ball mill, the total mass of the material is 1g, the ball-to-material ratio is controlled at 30:1, and the diameter of the zirconia ball mill used is 5mm. Then fix the sealed ball mill on a high-energy planetary ball mill and mill it at 550r / min for 7h. Then scrape the material from the wall of the ball mill, press the obtained powder into tablets, vacuum seal it in a quartz tube, and place it in a muffle furnace for calcination at 550℃ for 7h, with a heating rate of 0.5℃ / min. After cooling to room temperature, take out the modified flaky sulfide solid electrolyte material Li in the glove box. 6 PS 5 Cl-Co-L, grind and bottle for later use.
[0072] 3. Preparation of NCM811 composite cathode material
[0073] NCM811 and Li prepared in step 2 above 6 PS 5 Cl-Co-L and single-walled carbon nanotubes were weighed into a 25mL zirconia ball mill according to a mass ratio of 16:3:1. The total mass of the materials was 1g, the ball-to-material ratio was controlled to 20:1, and the diameter of the zirconia ball milling beads used was 3mm. The sealed ball milling jar was then fixed on a high-energy planetary ball mill at 400r / min for 4h. Finally, the NCM811 composite cathode material was obtained.
[0074] 4. Assembly of all-solid-state batteries
[0075] Weigh 100 mg of modified Li 6 PS 5 Cl solid electrolyte (Li 6 PS 5 Cl-Co-L) in a 10mm stainless steel tableting mold, press the electrolyte sheet at a pressure of 360MPa, then add 10mg of the composite positive electrode material prepared by the above method on one side of the electrolyte sheet, press it again at a pressure of 150MPa, then demould it, load it into the solid-state battery test mold, and then add a 10mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and apply a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature, at a rate of 0.1C, the first cycle charging capacity can reach 193mAh / g.
[0076] Comparative Example 1
[0077] The difference between this comparative example and Example 1 is that no Schiff base metal nanocomplex is used as an additive.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 1 is that the Ce Schiff base nanometal complex and Li 6 PS 5 The Cl mass ratio is 1:120.
[0080] Comparative Example 3
[0081] The difference between this comparative example and Example 1 is that the Ce Schiff base nanometal complex and Li 6 PS 5 The Cl mass ratio is 1:150.
[0082] Comparative Example 4
[0083] The difference between this comparative example and Example 1 is that the Ce Schiff base nanometal complex and Li 6 PS 5 The Cl mass ratio is 1:180.
[0084] Performance test case
[0085] The test standards or test methods are as follows:
[0086] First discharge specific capacity: 10mg positive electrode loading, 1C rate, 2.5V-3.7V;
[0087] The calculation formula for the first charge and discharge efficiency is: first charge and discharge efficiency = first discharge specific capacity / first charge specific capacity × 100%.
[0088] Table 1
[0089]
[0090]
[0091] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a solid electrolyte modified by a Schiff base metal nanocomplex, characterized in that: The method comprises the following steps: ball-milling a Schiff alkali metal nanocomplex and a solid electrolyte to obtain a mixed powder, and calcining the mixed powder to obtain a solid electrolyte modified by the Schiff alkali metal nanocomplex; the mass ratio of the Schiff alkali metal nanocomplex to the solid electrolyte is (1-7): (60-100); The metal in the Schiff base metal nanocomplex includes one of Ce, Ni and Co; The preparation method of the Schiff base metal nanocomplex comprises the following steps: 1) stirring and dissolving the solvent and o-vanillin, dropping 1,3-phenylenediamine, and stirring to form a Schiff base solution; 2) adding a metal salt to a Schiff base solution, stirring and heating, to obtain a metal complex precipitate; the metal salt comprises at least one of La(NO3)3, Ce(NO3)3, Gd(NO3)3, Ni(NO3)2, Cu(NO3)2, Mn(NO3)2, and Co(NO3)2; The molar ratio of the metal salt to the Schiff base is 1:1-1:2; the heating temperature is 50°C-150°C; the heating time is 30min-240min; 3) filtering the metal complex precipitate, washing and drying to obtain a powdery Schiff base metal nanocomplex.
2. The preparation method according to claim 1, characterized in that: The solid electrolyte is a sulfide solid electrolyte; the sulfide solid electrolyte includes at least one of Li3PS4, Li6PS5Cl and Li6PS5Cl-doped and modified solid electrolytes.
3. The preparation method according to claim 1, characterized in that: The calcination is carried out in a muffle furnace, the calcination temperature is 100°C-800°C, and the calcination time is 2h-15h.
4. A solid electrolyte modified by a Schiff base metal nanocomplex prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the solid electrolyte modified by the Schiff base metal nanocomplex as claimed in claim 4 in an all-solid-state battery.
Citation Information
Patent Citations
Ternary positive electrode material with shell-core structure, preparation method thereof and all-solid-state battery
CN111613782A
Trimetal Schiff base complex, preparation method thereof and application of trimetal Schiff base complex in catalyzing ring-opening copolymerization of epoxy compound
CN114853819A